Systematic mapping on the agility evaluation in software development organizations - Ortega-Ordóñez, Wilson Alfredo; Pardo-Calvache, César Jesús; Pino-Correa, Francisco José (Iteckne, 2019)
Agile software development approaches provide great benefits for organizations; however, their implementation is subject to many challenges. For organizations is important to know the level of agility achieved and the gaps in their transformation process in order to implement improvements in their processes and take advantage of the agile approaches. Keeping this in mind, this article presents a systematic mapping of the literature about the evaluation of agility in software development organizations. As a result, 18 studies were found, which were analyzed and compared taking into account the type of study, the relationship of the evaluation with the principles and agile values, the defined evaluation criteria, the validation methods used, and the proposed tools. In addition, the factors that influence the assessment of agility and the aspects that motivate the interest in this research stream are exposed.